Principles of corporate finance - Levy, Haim. (South-Western College, 1998)
This book is divided into seven parts: The financial environment; Project evaluation; Portfolio and capital budget decisions; Long-term financing; Capital structure and dividend policy; Financial Planning; and Shoort-Term financial management.